2015
DOI: 10.1503/cjs.011914
|View full text |Cite
|
Sign up to set email alerts
|

Traffic in the operating room during joint replacement is a multidisciplinary problem

Abstract: Traffic in the operating room during joint replacement is a multidisciplinary problemBackground: Door openings disrupt the laminar air flow and increase the bacterial count in the operating room (OR). We aimed to define the incidence of door openings in the OR during primary total joint arthroplasty (TJA) surgeries and determine whether measures were needed and/or possible to reduce OR staff traffic. Methods:We recorded the number of door openings during 100 primary elective TJA surgeries; the OR personnel wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 12 publications
(16 reference statements)
1
20
0
Order By: Relevance
“…Our study showed that the hybrid OR was most crowded during phase 3 when the wound was open and the endovascular procedure was being performed. Traffic flow, which is associated with the risk for postoperative infections (Bedard, Pelletier‐Roy, Angers‐Goulet, Leblanc, & Pelet, ), was also judged to be high and largely avoidable (Katz, ). Beyond the high number of people during phase 3, our analysis showed that in this specific phase of the procedure, the work was restricted to a few number of staff categories while the rest of the attending people were less active or not at all involved in the patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the hybrid OR was most crowded during phase 3 when the wound was open and the endovascular procedure was being performed. Traffic flow, which is associated with the risk for postoperative infections (Bedard, Pelletier‐Roy, Angers‐Goulet, Leblanc, & Pelet, ), was also judged to be high and largely avoidable (Katz, ). Beyond the high number of people during phase 3, our analysis showed that in this specific phase of the procedure, the work was restricted to a few number of staff categories while the rest of the attending people were less active or not at all involved in the patient care.…”
Section: Discussionmentioning
confidence: 99%
“…The laminar airflow system is equipped with high-efficiency particulate air (HEPA) filters, which filter the recirculated air [13,38,79]. The movement and presence of staff in the OR may negatively influence the laminar flow, so the number of people in the OR must therefore be minimised [13,80,81]. Also, the doors of an OR must be closed as much as possible, because every time the door opens, the pressure drops and turbulence in air movements occur, contributing to wound contamination [80].…”
Section: Operative Environmentmentioning
confidence: 99%
“…The movement and presence of staff in the OR may negatively influence the laminar flow, so the number of people in the OR must therefore be minimised [13,80,81]. Also, the doors of an OR must be closed as much as possible, because every time the door opens, the pressure drops and turbulence in air movements occur, contributing to wound contamination [80]. To reduce the frequency of door openings, Birgand et al suggest a more practical storage of frequently used materials, advanced communication systems and an improved organisation of surgical team shift changes [79,82].…”
Section: Operative Environmentmentioning
confidence: 99%
“…Several studies have evaluated the incidences and causes of DOs during elective total joint arthroplasties (TJAs) [8,18,20e22]. Rates of 0.19/min to 0.65/min DOs for primary, and 0.84/min for revision TJAs have been reported [3,18,20,21]. The highest percentage of DOs occurs during the preincision [18] or postincision periods [10].…”
mentioning
confidence: 99%
“…The highest percentage of DOs occurs during the preincision [18] or postincision periods [10]. The majority of the traffic constitutes the circulating nurses, followed by surgical implant representatives, and then the anesthesia and orthopedic staff [18,20,21]. The most frequently reported single reason for DOs is getting supplies, along with gathering and transferring information.…”
mentioning
confidence: 99%